Tourist Satisfaction at The Tourist Attraction Nimo Highland Pangalengan Bandung District - Andira, Daffa Ahmad; Raharjo, Tito Pandu; Maulida, Rata Gema (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Nimo Highland is an artificial tourist attraction that is the destination of choice for local tourists in Pangalengan District, located in Bandung Regency, West Java. However, the Nimo Highland tourist attraction still needs to be solved, contributing to decreased tourist satisfaction, the remarkably high price of entrance tickets, and a large amount of rubbish. It is a complaint from tourists who have visited the Nimo Highland tourist attraction and can cause dissatisfaction among visitors to other Nimo Highland tourist attractions. Research data analysis uses quantitative techniques, namely the Kano method. The Kano method is a technique that emphasizes the classification of product attributes in a company or service and evaluates how effectively the product or service meets consumer satisfaction. Kano techniques are categorized into mandatory, basic, one-dimensional, interesting, indifferent, doubtful, and reversal. Using this methodology, researchers can conclude the characteristics that are indicators of the level of satisfaction experienced by tourists. The research results show that of the 23 criteria with categories, the attributes included in One Dimensional are that the Nimo Highland tourist attraction meets the expectations of tourism uniqueness and diversity, and the remaining attributes fall into the Attractive category.